Tindak Pidana Penganiayaan yang Diakibatkan Mengkonsumsi Minuman Beralkohol Oleh Anak dari Aspek Kriminologi: (Studi Kasus Polres Gorontalo Kota) - Madina Mulia Ahmad; Fence M. Wantu; Mohamad Taufiq Zulfikar Sarson (Lembaga Pengembangan Kinerja Dosen, 2024)
This thesis aims to examine criminological aspects related to criminal acts of abuse committed by children who consume alcoholic drinks, with a focus on the context of the Gorontalo City Police Department. The first problem formulation explores the criminological review of criminal acts of child abuse related to the consumption of alcoholic beverages. This study involves analysis of criminological factors that may influence such behavior, including environmental, family, and social influences. The second problem formulation explores efforts to overcome criminal acts of abuse by children related to the consumption of alcoholic beverages, especially those carried out by the Gorontalo City Police. The analysis focuses on prevention, detection and response strategies carried out by police officers in responding to these cases. Apart from that, this thesis also evaluates the effectiveness and obstacles faced by the authorities in dealing with this problem. The research method used involves a qualitative approach with case studies as the main research design. Data was obtained through interviews with police officers, document analysis, and direct observation of the situation in the field. It is hoped that the results of the research will contribute to further understanding of the criminological factors that influence criminal acts of abuse by children who consume alcoholic beverages, as well as provide recommendations for improving response strategies by the police.